Chromium-free high temperature anti-oxidation passivation agent for electrolytic copper foil

Through the use of chromium-free high-temperature anti-oxidation passivator, the environmental and health hazards of chromium in electrolytic copper foil are solved, and more efficient passivation performance is achieved, meeting environmental protection requirements, and reducing wastewater treatment costs.

CN116288305BActive Publication Date: 2025-01-07WUHAN OXIRAN SPECIALTY CHEM CO

Patent Information

Application Number
CN202211717034.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2025-01-07
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

The use of hexavalent chromium and chromate solutions in the anti-oxidation treatment of existing electrolytic copper foils has environmental pollution and health hazards, and the wastewater treatment cost is high, making it difficult to meet the increasingly severe environmental protection requirements, and at the same time, the anti-oxidation performance is insufficient.

Method used

Provide a chromium-free high-temperature anti-oxidation passivator, which consists of complexing agent, corrosion inhibitor, auxiliary corrosion inhibitor, anti-oxidation agent and wetting agent. The chromium-free passivator is formed by specific preparation methods and process steps, and the chromium-free passivator is formed by In the passivation treatment of electrolytic copper foil, the passivation temperature is room temperature, the pH value is adjusted to 1-3, and the passivation time is 6-10 seconds.

Benefits of technology

The chromium-free passivator does not contain carcinogens, which reduces the risk of environmental and human hazards, reduces the cost of wastewater treatment, and significantly improves the high-temperature antioxidant properties of electrolytic copper foil. The passivation film is baked at 180-200℃ for 1 hour The color does not change, far exceeds the industry standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004026545710000061
    Figure BDA0004026545710000061
  • Figure HDA0004026545720000011
    Figure HDA0004026545720000011
  • Figure HDA0004026545720000012
    Figure HDA0004026545720000012
Patent Text Reader

Abstract

The invention discloses a chromium-free high-temperature anti-oxidation passivator for electrolytic copper foil, wherein the passivator is composed of the following components: 10-22 g / L of a complexing agent; 2-6 g / L of a corrosion inhibitor; 1-3 g / L of an auxiliary corrosion inhibitor; 8-300 g / L of an antioxidant; 0.1-0.5 g / L of a wetting agent; and deionized water as a solvent. The passivator does not contain chromium, meets environmental protection requirements, saves wastewater treatment costs, and further improves the high-temperature anti-oxidation performance of the electrolytic copper foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, and in particular to a chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil and a passivation process thereof. Background Art

[0002] In order to protect the electrolytic copper foil from oxidation during transportation, storage and application in copper-clad laminates, printed circuit boards, lithium-ion batteries, etc., which will affect its adhesion, solderability, resistance performance, etc., it is necessary to perform anti-oxidation treatment on the copper foil during the production process of electrolytic copper foil. At present, the commonly used anti-oxidation treatment is hexavalent chromium passivation, that is, immersion passivation in chromic acid solution or electrolytic passivation in chromate solution. Both methods require the use of Cr(VI). Cr(VI) is a highly toxic and carcinogenic substance that seriously harms the environment and human health, and the cost of wastewater treatment is high. The EU WEES and RoHS directives strictly restrict the use of Cr(VI). Therefore, in order to meet the increasingly stringent environmental protection requirements and further improve the anti-oxidation performance of the passivation film, a chromium-free passivator is urgently needed to replace the existing chromic acid and chromate passivation processes. Summary of the invention

[0003] Based on the above deficiencies in the prior art, the technical problem solved by the present invention is to provide a chromium-free high-temperature anti-oxidation passivator and a passivation process thereof. The passivator does not contain chromium, meets environmental protection requirements, saves wastewater treatment costs, and further improves the high-temperature antioxidant properties of electrolytic copper foil.

[0004] In order to solve the above technical problems, the present invention provides a chromium-free high-temperature anti-oxidation passivator for electrolytic copper foil, characterized in that the passivator is composed of the following components:

[0005] Complexing agent 10-22g / L;

[0006] Corrosion inhibitor 1-6g / L;

[0007] Auxiliary corrosion inhibitor 1-3g / L;

[0008] Antioxidant 8-300g / L;

[0009] Wetting agent 0.1-0.5g / L;

[0010] The solvent is deionized water.

[0011] As a preferred embodiment of the above technical solution, the chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil provided by the present invention further includes part or all of the following technical features:

[0012] As an improvement of the above technical solution, the pH value of the passivating agent is 1-3.

[0013] As an improvement of the above technical solution, the complexing agent is one or two of hydroxyethylidene diphosphonic acid, lactic acid, L-ascorbic acid, malic acid, succinic acid, tetrasodium glutamate diacetate, ethylenediaminetetraacetic acid, glycine, sulfosalicylic acid, aminosulfonic acid, citric acid, fluoroboric acid, fluorozirconic acid, and phosphoric acid.

[0014] As an improvement of the above technical solution, the corrosion inhibitor is one or two of sodium molybdate, ammonium molybdate, sodium tungstate, titanyl sulfate, nickel sulfate, nickel chloride, cobalt sulfate, and cobalt nitrate.

[0015] As an improvement of the above technical solution, the auxiliary corrosion inhibitor is one or two of lanthanum nitrate, cerium nitrate, sodium metavanadate, potassium fluorozirconate, manganese sulfate, and potassium dihydrogen phosphate.

[0016] As an improvement of the above technical solution, the antioxidant is one or two of acidic silica sol (effective content 25%), epoxy functionalized oligosiloxane, benzotriazole, methylbenzotriazole, tetramethylammonium silicate, and sodium methyl silicate.

[0017] As an improvement of the above technical solution, the wetting agent is one or two of decynediol polyoxyethylene ether, fatty alcohol block polyether, 2-ethylhexyl sulfate sodium salt, Gemini silane organic wetting agent JC-7000, maleic acid-acrylic acid copolymer

[0018] A method for preparing a chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil as described above comprises the following steps:

[0019] ① Add the calculated amount of deionized water into the preparation container;

[0020] ②Add calculated amount of complexing agent in sequence and stir thoroughly;

[0021] ③Add the calculated amount of corrosion inhibitor and auxiliary corrosion inhibitor in sequence, and stir at room temperature until completely dissolved;

[0022] ④ Slowly add the calculated amount of antioxidant and stir thoroughly;

[0023] ⑤ Add the calculated amount of wetting agent and stir thoroughly to obtain the chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil.

[0024] A method for using the chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil as described above, characterized in that it comprises the following steps:

[0025] Dilute the passivator by 5%-20% and adjust the pH value to 1-3. The passivation temperature is room temperature. The passivation method is immersion. The passivation time is 6-10s.

[0026] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0027] 1. The passivating agent of the present invention does not contain carcinogens such as hexavalent chromium and trivalent chromium, which not only reduces the risk of harm to the environment and human body caused by the passivating solution, but also reduces the cost of wastewater treatment, and meets the requirements of environmental friendliness and green environmental protection.

[0028] 2. The present invention refers to the electrolytic copper foil industry standard SJ / T 11483-2014 electrolytic copper foil for lithium ion batteries, and conducts a high-temperature baking test. The passivation film can be baked at 180-200°C for 1 hour without discoloration, and has a uniform appearance, which far exceeds the standard requirement of baking at 140°C for 15 minutes without discoloration.

[0029] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in combination with the preferred embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0031] Figure 1 This is a comparison of the color changes of unpassivated copper foil before and after baking at 180℃ for 60 minutes;

[0032] Figure 2 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 1 and baked at 180° C. for 60 minutes;

[0033] Figure 3 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 2 and baked at 180° C. for 60 minutes;

[0034] Figure 4 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 3 and baked at 180° C. for 60 minutes;

[0035] Figure 5 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 4 and baked at 180° C. for 60 minutes;

[0036] Figure 6 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 5 and baked at 180° C. for 60 minutes;

[0037] Figure 7 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 6 and baked at 180° C. for 60 minutes;

[0038] Figure 8This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 7 and baked at 180° C. for 60 minutes;

[0039] Fig. 9 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 8 and baked at 180° C. for 60 minutes;

[0040] Fig.10 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 9 and before and after being baked at 180° C. for 60 minutes;

[0041] Fig.11 This is a comparison chart of the color changes of the copper foil after being passivated with the passivation solution prepared in Example 10 and before and after being baked at 180° C. for 60 minutes. DETAILED DESCRIPTION

[0042] The specific implementation modes of the present invention are described in detail below, which is a part of this specification. The principles of the present invention are explained through examples. Other aspects, features and advantages of the present invention will become clear through the detailed description.

[0043] In the embodiment, the passivation process is as follows:

[0044] Copper foil polishing → pure water rinsing → activation (10% dilute sulfuric acid) → pure water rinsing → sealing (normal temperature) → squeezing water → hot air drying → high temperature baking test.

[0045] Example 1

[0046] Lactic acid 15g / L, L-ascorbic acid 1.5g / L, sodium molybdate 5g / L, cerium nitrate 1g / L, acidic silica sol (effective content 25%) 200g / L, decynediol polyoxyethylene ether 0.1g / L, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0047] Example 2

[0048] Sulfosalicylic acid 12g / L, fluoroboric acid 2g / L, sodium molybdate 3g / L, manganese sulfate 1g / L, epoxy functionalized oligosiloxane 5g / L, benzotriazole 3.6g / L, Gemini silane organic wetting agent JC-7000 0.3g / L, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0049] Example 3

[0050] 10g / L tetrasodium glutamate diacetate, 5g / L phosphoric acid, 6g / L sodium tungstate, 2g / L potassium fluorozirconate, 10g / L epoxy functionalized oligosiloxane, 1.5g / L sodium methyl silicate, 0.5g / L fatty alcohol block polyether, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0051] Example 4

[0052] 8g / L hydroxyethylidene diphosphonic acid, 6g / L citric acid, 6g / L ammonium molybdate, 2g / L lanthanum nitrate, 10g / L epoxy functionalized oligosiloxane, 1.5g / L tetramethyl ammonium silicate, 0.5g / L maleic acid-acrylic acid copolymer, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0053] Example 5

[0054] Malic acid 8g / L, ethylenediaminetetraacetic acid 6g / L, nickel sulfate 6g / L, sodium metavanadate 1g / L, tetramethylammonium silicate 8g / L, methylbenzotriazole 2g / L, 2-ethylhexyl sulfate sodium salt 0.5g / L, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0055] Example 6

[0056] 8g / L citric acid, 8g / L sulfosalicylic acid, 3g / L titanyl sulfate, 2g / L potassium dihydrogen phosphate, 12g / L sodium methyl silicate, 8g / L benzotriazole, 0.5g / L decynediol polyoxyethylene ether, and the rest is deionized water. The solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0057] Example 7

[0058] Succinic acid 10g / L, fluorozirconic acid 5g / L, sodium tungstate 6g / L, potassium fluorozirconate 2g / L, acidic silica sol (effective content 25%) 250g / L, Gemini silane organic wetting agent JC-7000 0.3g / L, the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 5%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0059] Example 8

[0060] Sulfosalicylic acid 15g / L, glycine 5g / L, sodium molybdate 3g / L, nickel chloride 3g / L, sodium metavanadate 2g / L, epoxy functionalized oligosiloxane 10g / L, tetramethyl ammonium silicate 5g / L, fatty alcohol block polyether 0.5g / L, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0061] Example 9

[0062] 8g / L of malic acid, 8g / L of L-ascorbic acid, 6g / L of titanium sulfate, 0.5g / L of lanthanum nitrate, 2g / L of potassium dihydrogen phosphate, 300g / L of acidic silica sol (effective content 25%), 0.3g / L of sodium 2-ethylhexyl sulfate, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0063] Example 10

[0064] 10g / L tetrasodium glutamate diacetate, 10g / L succinic acid, 3g / L nickel chloride, 3g / L cobalt nitrate, 1g / L potassium fluorozirconate, 1g / L sodium metavanadate, 8g / L methylbenzotriazole, 5g / L tetramethylammonium silicate, 0.1g / L maleic acid-acrylic acid copolymer, and the rest is deionized water. The prepared solution is a concentrated solution, which needs to be diluted by 3%-20% when used, with a pH value of 1-3, and the copper foil is soaked and passivated for 6-10s at room temperature, washed with water, and dried with hot air.

[0065] Table 1. Passivation film baking test conditions and evaluation criteria

[0066]

[0067] Figure 1 This is a comparison of the color changes of unpassivated copper foil before and after baking at 180℃ for 60 minutes; Figures 2 to 11 The color of the passivation film obtained by using the passivation solutions prepared in Examples 1-10 respectively and following the same passivation process is changed after baking at 180°C for 60 minutes. Figure 1-11 By comparison, it can be seen that the copper foil passivated with the chromium-free high-temperature anti-oxidation passivator of the electrolytic copper foil of the present invention has greatly improved anti-oxidation performance, and can be baked at 180°C for 60 minutes without discoloration, and has a uniform appearance, which exceeds the requirement of 140°C baking for 15 minutes without discoloration stipulated in the electrolytic copper foil industry standard SJ / T11483-2014.

[0068] The raw materials listed in the present invention, as well as the upper and lower limits and interval values ​​of the raw materials of the present invention, and the upper and lower limits and interval values ​​of the process parameters (such as temperature, time, etc.) can all realize the present invention, and the embodiments are not listed one by one here.

[0069] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil, characterized in that: The passivator is composed of the following components: Complexing agent 10-22 g / L; Corrosion inhibitor 2-6 g / L; Auxiliary corrosion inhibitor 1-3 g / L; Antioxidant 8-300 g / L; Wetting agent 0.1-0.5 g / L; The solvent was deionized water; The antioxidant is one or two of acidic silica sol, epoxy functionalized oligosiloxane tetramethyl ammonium silicate and sodium methyl silicate.

2. The chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil according to claim 1, characterized in that: The pH value of the passivating agent is 1-3.

3. The chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil according to claim 1, characterized in that: The complexing agent is one or two of lactic acid, L-ascorbic acid, malic acid, succinic acid, tetrasodium glutamate diacetate, glycine, sulfosalicylic acid, aminosulfonic acid, fluoroboric acid, fluorozirconic acid, and phosphoric acid.

4. The chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil according to claim 1, characterized in that: The corrosion inhibitor is one or two of sodium molybdate, sodium tungstate and titanyl sulfate.

5. The chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil according to claim 1, characterized in that: The auxiliary corrosion inhibitor is one or two of lanthanum nitrate, cerium nitrate, sodium metavanadate, potassium fluorozirconate and manganese sulfate.

6. The chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil according to claim 1, characterized in that: The wetting agent is one or two of decynediol polyoxyethylene ether, fatty alcohol block polyether, 2-ethylhexyl sulfate sodium salt, Gemini silane organic wetting agent JC-7000, and maleic acid-acrylic acid copolymer.

7. A method for preparing a chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil as claimed in any one of claims 1 to 6, characterized in that: The following steps are included: ① Add the calculated amount of deionized water into the preparation container; ②Add calculated amount of complexing agent in sequence and stir thoroughly; ③Add the calculated amount of corrosion inhibitor and auxiliary corrosion inhibitor in sequence, and stir at room temperature until completely dissolved; ④ Slowly add the calculated amount of antioxidant and stir thoroughly; ⑤ Add the calculated amount of wetting agent and stir thoroughly to obtain the chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil.

8. A method for using the chromium-free high-temperature anti-oxidation passivating agent for electrolytic copper foil as claimed in any one of claims 1 to 6, characterized in that: The following steps are included: Dilute the passivator by 5%-20% and adjust the pH value to 1-3. The passivation temperature is room temperature. The passivation method is immersion. The passivation time is 6-10 s.

Citation Information

Patent Citations

  • Copper material chromium-free passivator and preparation method and use method thereof

    CN112144049A

Cited By

  • Chromium-free copper corrosion inhibitor with good film-forming stability as well as preparation method and application of chromium-free copper corrosion inhibitor

    CN121781156A